Human rights in case of disasters: an approach to some emerging legal issues - Bautista-Hernáez, Andrés (My University, 2019)
Disasters may affect people around the world without distinction of race, age or status. A wide range of issues deals with disasters consequences (massive losses in human lives, environmental damages…); in the same way, internal or international displacement of populations to safety areas, together with environmental protection of these zones are some related aspects to be analysed. Some UN bodies have paid attention to these topics, such as the United Nations High Commissioner for Human Rights, through the Special Rapporteur on internally displaced persons, or the International Law Commission in its 2016 Draft articles on the protection of persons in the event of disasters. The protection of human rights in the event of disasters will be the main aspect of this research. Disasters will be studied according with the four phases of disaster management: prevention, preparedness, response and reconstruction. Jointly with this general approach, we will pay attention to specific emerging legal problems such as the relationship between legal rules on disasters and human rights instruments, and the effectiveness and applicability of such instruments, among others. The possibility to clarify the set of rules applicable in case of disaster, considering human rights conventional instruments as a backcloth is the leitmotiv of this research.
Keywords: Derechos humanos; Desastres; Congresos y conferencias; Human Rights; Disaster